PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV SD NEGERI III TONDANO: PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV SD NEGERI III TONDANO - Angel S.Z Mengko; Rorimpadey, Widdy H.F.; Margareta O. Sumilat (STKIP Subang, 2026)
This study aims to improve pupils’ learning outcomes in the subject of Integrated Natural Sciences (IPAS) through the implementation of the Problem-Based Learning (PBL) model in Year 4 at SD Negeri III Tondano. The research subjects consisted of 14 Year 4 pupils. The method used was Classroom Action Research (CAR), conducted over two cycles, with each cycle comprising the planning, implementation, observation and reflection stages. Data collection was carried out using observation techniques to observe learning activities and tests to measure students’ learning outcomes. The data obtained were analysed using a quantitative descriptive approach to determine the improvement in learning outcomes based on the scores achieved by the students. The results of the study showed a significant improvement in students’ learning outcomes. In Cycle I, the average student learning outcome reached 71.43% with a learning achievement rate of 57.14%, indicating that some students had not yet met the minimum achievement criteria. Following improvements to teaching in Cycle II through the optimisation of the PBL model, the average student learning outcome increased to 91.07% with a higher level of achievement. These findings indicate that the implementation of the Problem-Based Learning model is effective in improving student learning outcomes in the IPAS subject in Year 4 at SD Negeri III Tondano.